RADICAL SCAVENGING COMPOUNDS FROM THE AERIAL PARTS OF SOLENOSTEMON MONOSTACHYS BRIQ (LAMIACEAE) - Taiwo, Bamigboye Josiah; Obuotor, E.M; Onawunmi, Osarugue Grace; Ogundaini, Oguntuga Abiodun (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Solenostemon monostachys Briq. (Lamiaceae) is a weed widely used in ethno-medicine to treat infections and inflammatoryconditions but the active compounds are yet to be identified. This study isolated and identified the radical scavenging compounds from S.monostachys crude extract using diphenyl-1, 1-picryl hydrazyl (DPPH) to monitor the separation.Materials and Methods: The crude extract of the aerial parts of the plant was evaluated for antimicrobial activity using the agar diffusion test,anti-inflammatory test using carrageenan induced oedema of the rat paw and radical scavenging test using diphenyl-1, 1-picryl hydrazyl(DPPH). Repeated chromatographic separation of the ethyl acetate and n-butanol fractions on silica gel and Sephadex LH-20, monitored byDPPH bio-autographic assay resulted in the isolation of seven active compounds, which were identified using spectroscopic methods andcomparison with literature data.Results: The ethyl acetate and n-butanol fractions were the most active fractions and contained apigenin, apigenin glucuronide, luteolin, caffeicacid, methyl caffeate, rosmarinic acid and methyl rosmarinate as the radical scavenging compounds with EC50 values of 26.67 ± 0.31, 185.89 ±1.02, 5.35 ± 0.31, 3.92 ± 0.06, 13.41 ± 0.18, 4.99 ± 0.10, 5.97 ± 0.08 μg/ml respectively compared with 2.32 ± 0.08 μg/ml for quercetin as thereference standard.Conclusion: The isolated compounds are reported for the first time in this plant. The presence of the compounds in S. monostachys P. Beauv.(Briq.) (Lamiaceae) may provide justification for some of the ethnomedicinal uses of the plant in infections and inflammatory conditions.